2018
DOI: 10.1136/bmjopen-2018-021617
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of fasting glucose for gestational diabetes mellitus screening in Mexican adolescents based on International Association of Diabetes and Pregnancy Study Groups criteria: a diagnostic accuracy study based on retrospective data analysis

Abstract: ObjectiveTo evaluate fasting plasma glucose (FPG) as a screening test for gestational diabetes mellitus (GDM) among Mexican adolescents using International Association of Diabetes and Pregnancy Study Groups criteria.DesignRetrospective cohort study.SettingLevel-three medical institution in Mexico City.ParticipantsThe study population comprised 1061 adolescent women aged 12–19 years with singleton pregnancies, who underwent a 75 g oral glucose tolerance test (OGTT) between 11 and 35 weeks of gestation.Primary a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 28 publications
0
5
0
1
Order By: Relevance
“…which also indicated that the first-trimester FPG of 80 mg/dL (4.44 mmol/L) is a good predictor for GDM [17]. The results by Reyes et al showed that the cutoff value of FPG of 90 mg/dL (5.0 mmol/L) was helpful to avoid unnecessary OGTT in 0.7% of pregnant women [18]. Different studies all highlighted the usefulness and importance of using FPG alone for the diagnosis of GDM.…”
Section: Discussionmentioning
confidence: 99%
“…which also indicated that the first-trimester FPG of 80 mg/dL (4.44 mmol/L) is a good predictor for GDM [17]. The results by Reyes et al showed that the cutoff value of FPG of 90 mg/dL (5.0 mmol/L) was helpful to avoid unnecessary OGTT in 0.7% of pregnant women [18]. Different studies all highlighted the usefulness and importance of using FPG alone for the diagnosis of GDM.…”
Section: Discussionmentioning
confidence: 99%
“…GD is usually underdiagnosed, since the various reported prevalence values depend on the studied population and method used; furthermore GD diagnosis often depend on the population or geographical area and evidence to support the diagnostic process [25] , [26] , [27] , [28] .…”
Section: Discussionmentioning
confidence: 99%
“…First, we used fasting capillary blood glucose to diagnose GDM due to a lack of resources for oral glucose tolerance tests, which might affect the strength of recommendations. However, various studies have reported fasting capillary glucose as the most sensitive and specific test56 57 and recommended to be conducted in resource-limited settings 56. Second, even though capillary blood glucose is recommended in resource-limited settings, it is less sensitive than venous blood glucose.…”
Section: Discussionmentioning
confidence: 99%